UJI FITOKIMIA DAN POTENSI ANTIOKSIDAN DARI EKSTRAK KULIT KAYU GARUNGGANG Cratoxylum arborecens (Vahl) Blume: UJI FITOKIMIA DAN POTENSI ANTIOKSIDAN DARI EKSTRAK KULIT KAYU GARUNGGANG Cratoxylum arborecens (Vahl) Blume - Haiyul Fadhli (JURNAL FARMASI GALENIKA, 2019)
Gerunggang (Cratoxylum arborescens (Vahl.) Blume) is one of the plants from Hypericaceae that has benefits. From several studies that showed Hypericaceae has antioxidant activity and potential as a source of natural antioxidants. An investigation on the antioxidant activity of gerunggang extract has been done using 1-1-diphenyl-2-picrylhydrazyl (DPPH) method. The extract was obtained by macerating the stem barks of cratoxylum arborescens using n-hexane, ethyl acetate and methanol respectively. The antioxidant activity test was performed quantitative using microplate reader with ascorbic acid as a standard. The result showed that IC50 value of n-hexane extract, ethyl acetate extract and methanol extract of gerunggang sequentially 82.058 μg/mL ; 12 µg/mL and 8.335 µg/mL. methanol extract has the highest antioxidant activity that is 8.335 µg/mL.